Analisis Kandungan Flavonoid pada Daun Kumis Kucing (Orthosiphon aristatus) di Desa Surabaya Kabupaten Lombok Timur - Riska, Irma Wati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Flavonoids are the largest group of phenolic compounds found in nature. The cat's whisker plant (Orthosiphon aristatus) is a plant that belongs to the Lamiaceae family. This plant is one of the many medicinal plants in Indonesia, and is often used by people for traditional medicine. This research aims to determine the flavonoid content found in cat's whisker leaves in Surabaya Village, East Sakra District, East Lombok Regency. This type of research is exploratory descriptive. The sample used was 392.6 grams of cat's whisker leaves. Data collection techniques are observation and documentation. The data analysis technique uses phytochemical screening and Gas Chromatography-Mass Spectroscopy (GC-MS) analysis. The research results showed that cat's whisker leaves contain flavonoids. The results of analysis using Gas Chromatography-Mass Spectroscopy (GC-MS) showed that 11 compounds were identified in the methanol extract of cat's whisker leaves (Orthosiphon aristatus). These compounds include: Methoxy, Phenyl-, Oxime, Cyclohexene, 1-methyl-4-(1-methylethenyl)-, (R)- (CAS) D-1,8, 1H-Pyrrole, 2,5-dihydro- , 2,3-Dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one, N-Acetylpyrrolidone, 1,6-Anhydro-Beta-D- Glucopyranose, Mome Inositol (12.57%), Pluchidiol (2.38%), Beta-D-Mannofuranoside,1-O- Undecenyl)-, Octadec-9–Enoic Acid, Octadecanoic Acid (CAS) Stearic Acid. The highest content of secondary metabolite compounds is Octadec-9-Enoic Acid (21.67%).